Pengaruh Independensi, Pengalaman Auditor, dan Kompetensi terhadap Kemampuan Auditor dalam Mendeteksi Kecurangan (Studi Kasus pada Kantor Akuntan Publik di Wilayah Jakarta Selatan) - Daniswari, Valda Della; Nurlatifah, Siti; Loen, Mishelei; Rahmah, Mulia (Program Studi Magister Manajemen Universitas Krisnadwipayana, 2025)
This study aims to examine the influence of independence, auditor experience, and competence on auditors' ability to detect fraud in Public Accounting Firms (KAP) located in South Jakarta. Using a purposive sampling approach, data were collected through questionnaires distributed to 71 auditors from various firms. Multiple regression analysis was employed to assess the relationship between the independent variables and the auditors' fraud detection ability. The results reveal that, partially, independence does not significantly affect the auditors' ability to detect fraud, while auditor experience and competence have a significant positive impact. Simultaneously, all three variables independence, experience, and competence—exert a significant combined effect on fraud detection capability. These findings underscore the importance of enhancing auditor professionalism through experience and skill development, offering both theoretical and practical contributions to the forensic audit literature in Indonesia. The implications of this research are relevant for regulators and audit institutions seeking to strengthen audit quality by focusing on individual auditor capabilities.